Answer:
Length of AB=Length of A'B' because they are corresponding sides.
you should definetely mark me brainliest ;)
Answer: Length of AB = Length of A′B′
Step-by-step explanation:
Given : Figure ABCD is rotated by 180 degrees about the origin in the counterclockwise direction to obtain figure A′B′C′D′.
We know that a rotation is a rigid motion which does not changes shape and size of the figure.
It means the corresponding side lengths are equal.
Thus , if Figure ABCD is rotated to form A′B′C′D′, then the corresponding sides of both of them are equal.
i.e. Length of AB = Length of A′B′
Length of BC = Length of B′C′
Length of CD = Length of C′D′
Length of DA = Length of D′A′
Hence, the statement best compares the lengths of the sides of the two figures : Length of AB = Length of A′B′
What is the answers of 2ft × 4ft
Answer:
8ft.
Step-by-step explanation: If you are finding he area, 2 times 4 equals 8, so the answer would be 8 feet.
Which two whole numbers lies between the square root of 445?
Evaluate 3(x-4)+2x-x^2 for x=5
Answer:
-12
Step-by-step explanation:
3(x-4)+2x^2
when x =5 , sub 5 into x
3(5-4)+2(5)-(5)^2
=15-12+10-25
=-12
Answer:
Step-by-step explanation:
3(x-4)+2x-x^2 first you should eliminate the parentheses
3x-12+2x-x^2 now replace x for 5
3(5)-12+2(5)-(5)^2
15-12+10-25
-12
7. Change the fraction 13/20 to a decimal.
Answer:
divide it using a calculator
Answer:
Step-by-step explanation:
0.65 is your answer
(8,5) and (x, -1); slope: -6
Answer:
9 = x; (9, -1)
Step-by-step explanation:
-y₁ + y₂\-x₁ + x₂ = m
-5 - 1\-8 + x
-8 + x = 1
+8 + 8
_________
x = 9
The denominator is set to equal one because the numerator already equals negative six, and all we have to do is divide it by a POSITIVE one to stay at negative six.
I am joyous to assist you anytime.
Given the function, d(t) = 50t, the variable t represents which of the following? Select all that apply. input output function independent variable dependend variable
will give brainlyist if you want it
Answer:
Input
Independent variable
Step-by-step explanation:
we know that
Independent variables, are the values that can be changed or controlled in a given model or equation
Dependent variables, are the values that result from the independent variables
we have the function
[tex]d(t)=50t[/tex]
In this problem
The function d(t) represent the dependent variable or the output
The variable t represent the independent variable or input
Answer:
input and independet variable
Step-by-step explanation:
4 thousands 7 hundreds = 47 _
Answer:
4700
Step-by-step explanation:
4 thousands = 4000
7 hundreds = 700
Add those numbers together and you get 4700
Hope this helps
what is the value of 6*7-3^2*9+4^3
please show work will give 5 stars and brainliest
-615
I'm assuming you meant this. (6*7) - (3^2) *(9+4^3)
(42) - (3^2) * (9+4^3)
(42) - (9) * (9+4^3)
(42) - (9) * (9+64)
(42) - (9) * (73)
42 - 657
-615
Hope this helps!
Is 0.6 repeated irrational?
Answer:
no. it is not because 0.6 is a decimal
Two numbers have a GCF of 6 one is 24 the other number is less than 30 what could the other number be ?
The other number could be 6. The GCF of 6 and 24 is 6, and 6 is less than 30.
The length of a school bus is 12.6meters.if 9 school buses park end to end with 2meters between each one, what’s the total length from the front of the first bus to the end of the last bus?
First, 12.6 times 9 is 113.4. So withouth the space, that is how long the busses are. Then you do 2meters times 8 is 16 meters between the busses. 113.4+16 equals 129.4, the final answer.
Answer: The total length from the front of the first bus to the end of the last bus is 129.4 meters.
Step-by-step explanation:
Hi, to answer this question we have to multiply:
The number of buses by the length of each one
12.6 x 9 = 113.4 metersThe number of spaces between buses by the length of each space.
Since there is no space in front of the first bus and behind the last bus, there are 8 spaces in between.
8 x 2 = 16 Adding both results: 16 + 113.4 =129.4 meters front to backFeel free to ask for more if needed or if you did not understand something.
is the solution of this equation extraneous?
Answer:
x = - 3 is extraneous
Step-by-step explanation:
Given
[tex]\sqrt{x+7}[/tex] - 1 = x ( add 1 to both sides )
[tex]\sqrt{x+7}[/tex] = x + 1 ( square both sides )
x + 7 = (x + 1)² ← distribute right side
x + 7 = x² + 2x + 1 ( subtract x + 7 from both sides )
0 = x² + x - 6 ← in standard form
0 = (x + 3)(x - 2) ← in factored form
Equate each factor to zero and solve for x
x + 3 = 0 ⇒ x = - 3
x - 2 = 0 ⇒ x = 2
As a check
Substitute these values into the equation and if both sides are equal then they are the solutions.
x = - 3 : [tex]\sqrt{-3+7}[/tex] - 1 = [tex]\sqrt{4}[/tex] - 1 = 2 - 1 = 1 ≠ - 3
x = 2 : [tex]\sqrt{2+7}[/tex] - 1 = [tex]\sqrt{9}[/tex] - 1 = 3 - 1 = 2
x = 2 is a solution and x = - 3 is extraneous
Good morning ☕️
____________________
Step-by-step explanation:
Look at the photo below for the answer.
:)
If you are writing an equivalent expression for 2^3 times 2^4, how many times would you write two as a factor?
Answer:
[tex]2^3(2^4)=2^{3+4}=2^7=2(2)(2)(2)(2)(2)(2)[/tex]
Step-by-step explanation:
You can write 2 as a factor of [tex]2^3 \times 2^4[/tex] 7 times
The given expression can be written mathematically as:
[tex]2^3 \times 2^4[/tex]
We can simplify the expression by using the rule of indices shown below:
[tex]a^b \times a^b = a^{b+c}[/tex]
Applying the rule above to the given expression:
[tex]2^3 \times 2^4\\\\2^{3+4}\\\\2^7[/tex]
Therefore [tex]2^3 \times 2^4 = 2^7[/tex]
You can write 2 as a factor of [tex]2^3 \times 2^4[/tex] 7 times
Learn more here: https://brainly.com/question/24282237
2x -5 = 15 two step equation
Answer:
x = 10
Step-by-step explanation:
collect like terms, so add 5 to both sides: 2x = 20
divide both sides by 2 to get the value of x: x = 10
Answer:
x=10
Step-by-step explanation:
first, add 5 to both sides. the -5 and +5 cancel out, and 15 + 6 is 20. 2x=20. now divide 2 on both sides. the 2s cancel out and 20/2 is 10, so x=10.
Triangle E F G is shown. Which statements regarding Triangle E F G are true? Select three options. E F + F G greater-than E G E G + F G greater-than E F E G minus F G less-than E F E F minus F G greater-than E G E G + E F less-than F G
The properties of triangle side lengths follow the Triangle Inequality Theorem, which states that the sum of any two sides of a triangle must be greater than the third side, leading to three correct inequalities for Triangle EFG.
Explanation:The question presented is related to the properties of triangle sides, specifically in relation to the inequality theorems that apply to triangles.
By understanding these properties, we can determine which statements about the lengths of the sides in triangle EFG are true.
The Triangle Inequality Theorem states that the sum of the lengths of any two sides of a triangle must be greater than the length of the third side.
This theorem gives rise to three inequalities that must hold true for any triangle:
EF + FG > EGEG + FG > EFEG + EF > FGTo assess which statements about Triangle EFG are true, we can compare them against the principles derived from the Triangle Inequality Theorem.
The following are the correct statements based on this theorem:
EF + FG > EGEG + FG > EFEG - FG < EFAny statement that contradicts these principles is false.
Therefore, the three true statements regarding Triangle EFG are that EF + FG is greater than EG, EG + FG is greater than EF, and EG - FG is less than EF.
The three true statements regarding Triangle EFG are:
- EF + FG > EG
- EG + FG > EF
- EG + EF < FG
Let's go through each option one by one:
1. E F + F G greater-than E G: To determine if this statement is true, we need to compare the lengths of EF and EG combined with FG. Let's say EF is 5 units long, FG is 3 units long, and EG is 7 units long. In this case, 5 + 3 is equal to 8, which is greater than 7. Therefore, this statement is true.
2. E G + F G greater-than E F: Similarly, to determine if this statement is true, we need to compare the lengths of EG and FG combined with EF. Using the same lengths as before, 7 + 3 is equal to 10, which is greater than 5. Therefore, this statement is true as well.
3. E G minus F G less-than E F: For this statement, we need to subtract the length of FG from EG and compare it to EF. Using the same lengths as before, 7 - 3 is equal to 4, which is less than 5. Therefore, this statement is false.
4. E F minus F G greater-than E G: Here, we need to subtract the length of FG from EF and compare it to EG. Using the same lengths as before, 5 - 3 is equal to 2, which is less than 7. Therefore, this statement is false.
5. E G + E F less-than F G: To check this statement, we need to compare the lengths of EG and EF combined with FG. Using the same lengths as before, 7 + 5 is equal to 12, which is greater than 3. Therefore, this statement is true.
Complete question :-
Age of car = 2 years.
Original cost = $14,995.
The current market value is $
Answer:
7,497.50 OR, 7,497 &1/2 in fraction form
Step-by-step explanation:
I got this answer by dividing 14,995 by 2 and got $7,497.50 hope this helps you mark as brailiest if best answer if any questions comment on this question below!! ThNks !!
Answer:
7,497.50
Step-by-step explanation:
Liliana eants to write an
Answer:
Step-by-step explanation:
Answer:
the new height will be:
d.168 inches
Answer:
168 inches
Step-by-step explanation:
Lourdes is making a frame in the shape of a parallelogram. She adds diagonal braces to strengthen the frame. Parallelogram A B C D is shown. Diagonals are drawn from point A to point C and from point D to point B and intersect at point E. The length of D E is (3 y + 6) centimeters, the length of E B is (5 y minus 10) centimeters, and the length of E C is (2 y + 4) centimeters. How long is the brace that connects points B and D? 8 cm 16 cm 30 cm 60 cm
Answer:
60 cm
Step-by-step explanation:
Parallelogram ABCD is shown in attached diagram. The diagonals of the parallelogram bisect each other, so
AE = EC
BE = ED
Ib DE = 3y + 6 cm, BE = 5y - 10 cm, then
[tex]3y+6=5y-10\\ \\3y-5y=-10-6\\ \\-2y=-16\\ \\2y=16\\ \\y=8\ cm[/tex]
Now, EC = 2y + 4, so
[tex]EC=2\cdot 8+4=16+4=20\ cm[/tex]
Since AE = EC, then AE = 20 cm
The brace that connects points B and D has the length
[tex]BD=BE+ED=3y+6+5y-10=8y-4=8\cdot 8-4=64-4=60\ cm[/tex]
The brace that connects points A and C has the length
[tex]AC=AE+EC=20+20=40\ cm[/tex]
Answer:
60cm
Step-by-step explanation:
simplify 3x + 6 x 2 - 5 x - x2
Answer:
5x^2 − 2x
Step-by-step explanation:
Let's simplify step-by-step.
=3x + 6x^2 + − 5x + − x^2
Combine Like Terms:
=3x + 6x^2 + − 5x + − x^2
=( 6x^2 + − x^2 ) + ( 3x + − 5x )
= 5x^2 + − 2x
Answer:
5x^2 − 2x
hope this helps!!
27. A tank holds 240litres of water. How much water is in the tank when it is full?
(a) 240 litres
(b) 192 litres
(c) 132 litres
Answer:
240 liters
Step-by-step explanation:
because the tank holds 240 liters so if it's full then it will be the same
In the tank, there are 240 liters of water, as mentioned in the given condition. Option A is correct.
Given that
A tank holds 240 liters of water.
Volume is defined as the mass of the object per unit density while for geometry it is calculated as profile area multiplied by the length at which that profile is extruded.
Here,
As mentioned in the condition the tank can hold 240 liters of water, so as of the given data when the tank is full there can only be 240 liters of water.
Thus, In the tank, there are 240 liters of water, as mentioned in the given condition. Option A is correct.
Learn more about Volume here:
https://brainly.com/question/1578538
#SPJ5
The line passing through the point (-2,5)and (1,a) is perpendicular to the line 2x-y-5=0, find the value of a
Answer:
a = 7/2
Step-by-step explanation:
2x - y - 5 = 0
2x = y + 5
y = 2x - 5
m = -1/2
y - 5 = -1/2(x - (-2))
y - 5 = -1/2(x + 2)
y - 5 = -x/2 - 1
y = -x/2 + 4
a = -1/2 + 4
a = 7/2
88.6 as a mixed number
88.6 as a mixed number is 14 2/3
Solve x2+6x=7 by completing the square.Which is the solution set of the equation?
Answer:
x = - 7, x = 1
Step-by-step explanation:
Given
x² + 6x = 7
To complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(3)x + 9 = 7 + 9
(x + 3)² = 16 ( take the square root of both sides )
x + 3 = ± [tex]\sqrt{16}[/tex] = ± 4 ( subtract 3 from both sides )
x = - 3 ± 4
x = - 3 - 4 = - 7
x = - 3 + 4 = 1
Solution set = { - 7, 1 }
What is the solution to the equation below?
5 + 6x = 2x - 7
A. x = -3
B. X = 1.5
C. x= -1.5
D. X = 3
[tex]\huge\boxed{\text{A.}\ x=-3}[/tex]
Start by subtracting [tex]2x[/tex] from both sides of the equation. Our goal is to isolate the variable. [tex]5+4x=-7[/tex]
Now, subtract [tex]5[/tex] on both sides. [tex]4x=-12[/tex]
Finally, divide both sides by [tex]4[/tex]. [tex]x=\boxed{-3}[/tex]
Answer:
A. x = -3
Step-by-step explanation:
5 + 6x = 2x - 7
5 + 7 = 2x - 6x
12 = -4x
12/-4 = x
-3 = x
What is the slope of the line that passes through the given points?
(2, 12) and (6, 11)
A. –1 over 4
B. 1 over 4
C. 4
D. –4
What is the slope of the line that passes through the given points?
(6, –1) and (–3, –1)
A. undefined
B. 0
C. –two-thirds
D. –start fraction 3 over 2 end fraction
Answer:
For points : (2, 12) and (6, 11)
, option A. is correct.
For points : (6, –1) and (–3, –1), option B. is correct
Step-by-step explanation:
We are given points in both the questions and we need to find the slope.
Slope refers to steepness of curve .It is basically change in y with change in x.
For two points [tex]P\left ( x_1,y_1 \right )\,,\,Q\left ( x_2,y_2 \right )[/tex], slope of line PQ is [tex]\frac{y_2-y_1}{x_2-x_1}[/tex]
For points : (2, 12) and (6, 11)
Let [tex]P\left ( x_1,y_1 \right )=(2, 12)\,,\,Q\left ( x_2,y_2 \right )=(6, 11)[/tex],
Slope is [tex]\frac{11-12}{6-2}=\frac{-1}{4}[/tex] i.e, - 1 over 4
So, option A. is correct.
For points : (6, –1) and (–3, –1)
Let [tex]P\left ( x_1,y_1 \right )=(6, -1)\,,\,Q\left ( x_2,y_2 \right )=(-3, -1)[/tex]
Slope is [tex]\frac{-1+1}{-3-6}=\frac{0}{-9}=0[/tex]
So, option B. is correct
The required slope of the lines with the given coordinates are as follow,
For first line option A. -1/4
For second line option B.0.
For the first set of coordinates of the line,
Points are (2, 12) and (6, 11)
let (x₁ , y₁ ) = (2, 12 )
( x₂ , y₂ ) = (6, 11 )
Slope of the line for the two coordinates (x₁ , y₁ ) = (2, 12 ) and
( x₂ , y₂ ) = (6, 11 ) is equal to
m = ( y₂ - y₁ ) / ( x₂ - x₁ )
Substitute the value ,
m = ( 11 - 12 ) / ( 6 - 2 )
= -1 / 4
For the second set of coordinates of the line,
Points are (6, -1) and (-3, -1)
let (x₁ , y₁ ) = (6, -1 )
( x₂ , y₂ ) = (-3, -1 )
Slope of the line for the two coordinates (x₁ , y₁ ) = (6, -1 ) and
( x₂ , y₂ ) = (-3, -1 ) is equal to
m = ( y₂ - y₁ ) / ( x₂ - x₁ )
Substitute the value ,
m = ( -1 - (-1) ) / ( -3 - 6 )
=0 / -9
= 0
Therefore, slope of the lines are option A. -1/4 and option B.0.
Learn more about slope here
brainly.com/question/3605446
#SPJ3
The camp cook made 1 1/2 pints of baked beans. Each serving of beans is 3/4 of a pint. How many servings of beans did the cook make?
Answer:
number of servings = 5 servings
Explanation:
We are given that each serving is 3/10 of a pint. To know the number of servings of 1.5 pints, we will simply use cross multiplication as follows:
1 serving ....................> 3/10 pint
?? servings ................> 1.5 pints
number of servings = (1.5*1) / (3/10)
number of servings = 5 servings
Hope this helps :)
Answer:
11/2-3/4
11-6/2=5/2
Step-by-step explanation:
Plz help me I need help
Answer:
Step-by-step explanation:
Solve the equation for X x+3/6 = x - 6 /3
The equation x + 3/6 = x - 6/3 cannot be solved for x, as simplification leads to 1/2 = -2, which is not possible, indicating a mistake in the provided equation.
Explanation:To solve the equation x + 3/6 = x - 6/3 for x, let's first simplify each side of the equation by reducing the fractions. This gives us:
x + 1/2 = x - 2
At this point, we can see that the variable x appears on both sides of the equation. To solve for x, we would normally try to isolate x on one side. However, if we attempt to subtract x from both sides, we will get:
1/2 = -2
This statement is not true, indicating that the original equation was incorrect or improperly written. If the equation only involved x on one side, we could use algebraic techniques to solve for x, but as it stands with this impossible equality, we cannot find a value for x that satisfies the equation. Therefore, it seems there may be a mistake in the transcription of the original problem.
There are 300 passengers on board an airplane. 2/3 of them are men, 1/4 are women and the rest are children. How many children are there?
Answer:
25.
Step-by-step explanation:
2/3 of 300 is 200
1/4 of 300 is 75
Answer:
25
Step-by-step explanation:
2/3 of 300 is 200
1/4 of 300 is 75
Prove that the quadrilateral with vertices (2,5) (4,8) (7,6) and (5,3) is a rectangel
Answer: Line slopes:
m1= 3/2 defined by points (5,3) and (7,6)
m2= -2/3 defined by points (7,6) and (4,8)
m3 = 3/2 defined by points (4,8) and (2,5)
m4 = -2/3 defined by points (2,5) and (5,3)
All comply the orthogonal slopes rule (90º)
Step-by-step explanation:
As those 4 point define a polygon, to check is that polygon is a rectangle, you need to compare the slopes of the lines defined by the 4 points and check that accomplish the following rule:
m1 = -(1/m2). this shows that the slopes are intersected in 90º angle.
Final answer:
By calculating the dot products of the direction vectors for adjacent sides, all of which are zero, and checking the distances of opposite sides, which are equal, we prove that the given quadrilateral is a rectangle.
Explanation:
To prove that a quadrilateral with given vertices is a rectangle, we must show that the quadrilateral has four right angles and opposite sides are equal. A right angle exists between two sides if the dot product of their direction vectors is zero, as this indicates perpendicularity. Equal length of opposite sides can be shown by the distance formula. We are given the vertices of the quadrilateral: (2,5), (4,8), (7,6), and (5,3).
Calculate the direction vectors of adjacent sides:
AB: (4-2, 8-5) = (2,3)
BC: (7-4, 6-8) = (3,-2)
CD: (7-5, 6-3) = (2,3)
DA: (2-5, 5-3) = (-3,2)
Check the dot products of the direction vectors of adjacent sides to confirm right angles:
AB · BC = (2)(3) + (3)(-2) = 6 - 6 = 0
BC · CD = (3)(2) + (-2)(3) = 6 - 6 = 0
CD · DA = (2)(-3) + (3)(2) = -6 + 6 = 0
DA · AB = (-3)(2) + (2)(3) = -6 + 6 = 0
Use the distance formula to confirm equal lengths of opposite sides:
AB = √((4-2)² + (8-5)²) = √(13)
CD = √((7-5)² + (6-3)²) = √(13)
BC = √((7-4)² + (6-8)²) = √(13)
DA = √((2-5)² + (5-3)²) = √(13)
Since all adjacent sides are perpendicular and opposite sides are of equal length, the quadrilateral is a rectangle.